2013
DOI: 10.4315/0362-028x.jfp-12-526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lime Juice on Vibrio parahaemolyticus and Salmonella enterica Inactivation during the Preparation of the Raw Fish Dish Ceviche

Abstract: OF THE THESISThe effect of lime juice on Vibrio parahaemolyticus and Salmonella enterica inactivation In experiments with Salmonella at room temperature, a mean log reduction of 0.8 was observed while at refrigeration temperature a mean log reduction of 2.1 was observed.iii Reduction in Vibrio parahaemolyticus could only be estimated based on starting levels and detection limits as the plate counts were always below the detection limit for all the times studied (10-150 minutes), both at room and refrigeration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
2
10
1
Order By: Relevance
“…Our result is supported by Mathur's findings [28] that lime juice is effective in inactivation of both V. parahaemolyticus and Salmonella Enterica. He also found that refrigeration while marinating the fish had a significant impact on Salmonella reduction.…”
Section: Decontamination Of Shrimp Using Organic Acidssupporting
confidence: 88%
See 2 more Smart Citations
“…Our result is supported by Mathur's findings [28] that lime juice is effective in inactivation of both V. parahaemolyticus and Salmonella Enterica. He also found that refrigeration while marinating the fish had a significant impact on Salmonella reduction.…”
Section: Decontamination Of Shrimp Using Organic Acidssupporting
confidence: 88%
“…Our observation that lemon juice was more effective at refrigerator temperature than lemon at room temperature at 0.25 and 1 h is supported by Mathur's postulation [28] that when cells are exposed concurrently to two stresses (acid and refrigeration), this results in a greater reduction.…”
Section: Decontamination Of Shrimp Using Organic Acidssupporting
confidence: 68%
See 1 more Smart Citation
“…Typically, ceviche is made by marinating uncooked tilapia in vinegar or citrus juice or a mixture of lime and other citrus juices, and seasoning them with salt, cucumber, onion, pepper, and other spices. Other major recipe variables include the temperature (either room or refrigerator) and time of marination (Mathur & Schaffner, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Sallam et al (2008) reported similar results where Vibrio was not detected in marinated Pacific saury treated with marinating solutions containing either 12% NaCl and 2% acetic acid or 12% NaCl and 3% acetic acid and stored at 4°C for 90 days. V. parahaemolyticus was also reported to be reduced to below detection limits (∼5-log reduction) with the use of lime juice for marinating (Mathurand et al, 2013). Finally, there are no records of association of Vibrio spp.with canned food.…”
Section: Vibriomentioning
confidence: 99%